Comparative evaluation of push-out bond strength of a MTA-based root canal sealer - Eduardo Diogo Gurgel-Filho; Felipe Martins Leite; Jaírton Benício de Lima; João Paulo Chaves Montenegro; Flávia Saavedra; Emmanuel João Nogueira Leal Silva (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the bond strength to root dentin of three root canal sealers: a mineral trioxide aggregate (MTA)-based sealer (MTA Fillapex®), an epoxy resin-based sealer (AH Plus®), and a zinc oxide eugenol-based sealer (EndoFill®). Methods: Thirty extracted single-root human teeth of similar sizes and circular canals were prepared using #3 and #2 Gates Glidden drills in the cervical portion of the canal and K3® rotary instruments to a size #25/0.06 to working length. Irrigation with 0.5 mL 2% chlorhexidine gel was used before and 1 mL saline after each instrument. The smear layer was removed with 3 mL 17% EDTA for 3 min. The samples were sectioned horizontally into eight 1±0.1 mm-thick serial slices and then the push-out test was carried out. Two-way analysis of variance (ANOVA) and the post-hoc Tukey test were used for the analysis of the data with a significance level of 5%. Results: AH Plus presented significantly higher bond strengths (p<0.05) than the other sealers, while MTA Fillapex showed the lowest bond strengths (p<0.05). Conclusions: The present study concluded that EndoFill® sealer and MTA FillApex® core combination were not superior to AH Plus® sealer and gutta-percha core combination.